Pengaruh Kemampuan Manajerial Terhadap Minat Masyarakat Untuk Membayar Zakat di Baitul Mal Aceh Tamiang - Andi Tarlis; Imil Indra Kesuma (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2022)
In Islamic teachings the way to alleviate poverty already exists in one of its pillars, namely by paying zakat. This study explains the public's interest in paying zakat and the managerial ability of Baitul Mal Aceh Tamiang. The main objective of this study was to determine the effect of managerial ability on the public’s interest in paying and the managerial ability of Baitul Mal Aceh Tamiang. It is a quantitative research using primary and secondary data collected through questionnaire and interview. The populations in this study are 70 muzakkis with 41 samples taken using purposive sampling method. Data analysis techniques used are validity test, reliability test, normality test, and simple regression analysis with the help of SPSS. The results show that the influence of managerial ability on public interest is 38% while the remaining 62% is influenced by other factors outside this research. The influence of knowledge about usury towards saving interest has t count of 2.815> and t table 1.683. The coefficient value of the managerial ability variable is 0.298 which means that the independent variable has positive effect on the dependent variable. So that it can be concluded that managerial ability has a positive and significant effect on people's interest in paying zakat in the Baitul Mal Aceh Tamiang.